Evaluation of the quality of referral letters: experience of a Brazilian oral medicine service - Camila Real Delegá Rodrigues; Patrícia Maria Fernandes; Alan Roger Santos-Silva; Pablo Agustin Vargas; Marcio Ajudarte Lopes (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: Optimizing the quality of referral letters could be the first step to a correct clinical approach for patients. Referral letters should be legible and contain the necessary information to avoid delaying the patient's diagnosis and treatment. However, to date, few studies have been conducted on how referrals are performed in Brazil. Knowledge regarding the quality of referral letters can provide information to better guide health care professionals. This study was aimed at analyzing all referrals received by a single oral medicine service in Brazil. Referral letters were classified into poor, regular, good, and excellent based on key items concerning the primary morphology of the lesion, location, diagnostic hypothesis, symptomatology, time of evolution, consistency, size, and limits. A total of 500 referral letters were evaluated, including 271 (54.2%) from a private service and 229 (45.8%) from a public service. Dentists and physicians had written 475 (95%) and 25 (5%) referral letters, respectively. Among the 500 referrals analyzed in this study, the number of regular, poor, good, and excellent referrals was 236 (47.2%), 203 (40.6%), 58 (11.6%), and one (0.6%), respectively, showing a lack of important clinical information in referrals.